Edukasi Dan Sosialisasi Ekspor Dan Impor Pada Pelaku Usaha Ekonomi Kreatif dan PKK di Depok Jawa Barat - Hendi Prihanto; Usmar Usmar; Selfiani Selfiani; Yudistira Adwimurti; Sismiati Sismiati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This paper discusses the important role of education and socialization in the context of exports and imports for creative economy entrepreneurs and PKK in Depok, West Java. In the era of globalization, understanding the export and import process is the main key in developing local economic potential. This paper focuses on educational efforts and socialization activities that can provide in-depth understanding to business actors regarding the benefits, regulations, and opportunities related to exports and imports. The learning method is in the form of a face-to-face seminar between all participants and facilitators held at Griya Sakinah Kav. Tanah Baru, Beji Depok, West Java. The emphasis is on practical, theoretical, as well as case knowledge and provides opportunities for participants to ask questions about exports and imports. Thus, participants better understand the export and import processes and procedures effectively. The expected result of this education and socialization is that participants gain comprehensive knowledge about exports and imports, help improve participants' skills, allowing them to utilize international markets more efficiently. This socialization is an important factor in shaping positive perceptions of export and import activities, as well as building networks that support the exchange of information and experience between business actors. Through this community service activity, it is expected to be an opportunity for creative economy business actors and PKK in Depok related to exports and imports so as to realize capacity building and active participation in international trade.